Pelatihan Pembuatan Batako Desa Jatimulyo Kecamatan Kauman Kabupaten Tulungagung Lokal - Fatmawati, Laily; Supriono, Lyya; Amadi, Dwi Nor (JURNAL DAYA-MAS, 2021)
Abstract— The majority of the people of Jatimulyo Village are involved in agriculture, to broaden their horizons and hone the creativity of the younger generation to be more developed among them by providing skills training in making concrete blocks which can later be used to prepare business for the procurement sector. Besides being able to reduce the unemployment rate, it can also improve the community's economy. Increasingly, development growth in the construction sector tends to increase so that market opportunities for material marketing, especially concrete blocks, will certainly increase. The results obtained by conducting brick building training are to increase the insight and skills of youth youth in making concrete blocks, as well as to improve the welfare of youth youth and village residents in particular. Keywords—: concrete blocks; socialization; material; tools.